A potential zoonotic threat: First detection of Baylisascaris procyonis in a wild raccoon from Austria. Issue 6 (7th January 2021) - Duscher, Georg Gerhard; Frantz, Alain C.; Kuebber‐Heiss, Anna; Fuehrer, Hans‐Peter; Heddergott, Mike
Abstract: Baylisascaris procyonis is a common gastrointestinal parasite of raccoons ( Procyon lotor ) in their native range, and both have been introduced to Europe. Humans may ingest ascarid eggs shed via the racoons' faeces, and this could lead to severe infections affecting the central nervous system. Here, we report the first occurrence of B. procyonis in Austria. The parasite was detected in a two‐year‐old male raccoon that was road‐killed in November 2019 near Hittisau (Vorarlberg). Genetic profiling provided strong evidence that the raccoon (and its parasite) originated from the nearest German raccoon population. The first finding in Austria highlights the need for monitoring the parasite and information of the public and practitioners.